Implementation of the Merdeka Curriculum (IKM) in Enhancing Students’ Autonomy and Critical Thinking Skills at SDN Suci Kasemen, Serang City - Sudistiana, vina; Abdul Baqi, Fuad; Sariwardani, Andriani (Center of Language and Cultural Studies [CLCS], 2024)
This study aims to analyze the implementation of the Merdeka Curriculum in enhancing student autonomy and critical thinking skills at SDN Suci Kasemen Kota Serang. Employing a qualitative approach with a case study method, data were collected through in-depth interviews, participatory observation, and documentation. The findings indicate that project-based learning, which is the core of IKM, effectively enhances student autonomy in taking initiatives and being responsible for their learning process. Furthermore, students' critical thinking skills develop through information analysis, logical argumentation, and data-driven problem-solving. However, challenges in implementing Merdeka Curriculum include teacher readiness, limited supporting facilities, and inadequate parental involvement. This study emphasizes the importance of teacher training, resource strengthening, and collaboration among schools, parents, and the government in supporting the successful implementation of Merdeka Curriculum. With the right strategies, the Implementation of Merdeka Curriculum has the potential to become a crucial instrument in developing students' skills in 21st-century.